Physiological responses of oil palm (Elaeis quineensis Jaq.) seedlings to sulphur dioxide fumigation. - Awang, Muhamad; A. B., Ibni; M., Azman (1986)
A fumigation experiment was designed to determine the effects of varying concentrations and durations exposure to SO2 on one year old of oil palm seedlings. Plants were exposed to 0.005,0.1,0.1,0.5,1.0 and 3.0 ppm of SO2 for 1,2 and 3h in a controlled environment chamber. The control and fumigated plants were periodically analysed for leaf diffusive resistance,transpiration rate,potassium leakage,chlorophyll content of the leaf tissue and visible foliar injury. Exposure to high concentration and longer period has led to increase in K+ leakage,rate of transpiration (decrease in adaxial leaf diffusive resistance),visible injury was primarily restricted to intermediate age leaves and appeared as necrosis at marginal and interveinal areas. The result seemed to suggest that the threshold level of the visible foliar injury was 0.3ppm after one hour exposure. This was highly correlated with other physiological parameters.